Regulation of insulin secretion by the post-translational modifications - Yang, Chunhua; Wei, Mengna; Zhao, Yanpu; Yang, Zhanyi; Song, Mengyao; Mi, Jia; Yang, Xiaoyong; Tian, Geng (Frontiers in Cell and Developmental Biology, 2023)
Protein posttranslational modification (PTM) has a significant impact on cellular signaling and function regulation. In pancreatic β cells, PTMs are involved in insulin secretion, cell development, and viability. The dysregulation of PTM in β cells is clinically associated with the development of diabetes mellitus. Here, we summarized current findings on major PTMs occurring in β cells and their roles in insulin secretion. Our work provides comprehensive insight into understanding the mechanisms of insulin secretion and potential therapeutic targets for diabetes from the perspective of protein PTMs.